Optimization of Manufacturing Company's Production Process Using Lean Six Sigma - Fortuna, Dhea; Yuliawati, Evi (Jurnal Teknologi, 2024)
In the manufacturing industry, product quality is the main focus. Companies must ensure products meet quality standards. PT. Preshion Engineering Plastec Surabaya is a company that produces plastec supporting components. The object of this study is Yamaha emblem assy products. With Lean six sigma using DMAIC (Define, Measure, Analyze, Improve, Control) methodology to improve production processes. In addition, it improves the efficiency and effectiveness of the production process, improves product quality. The emblem assy product from CTQ shows that there are 4 defects that occur, namely outgoing rays, dirty, shin marks, and short mold. So that the DPMO (Defect Per Million Opportunies) value from January to March 2023 is 159784.715 with an average of 13315.39 and produces a sigma value of 45.0011 with an average of 3.75. Identification of the root causes of defects in Emblem assy products that are dominant with fishbone diagrams, namely dirty injection machines and material mixing machines, old machine age. It is hoped that further research can identify the factors that cause product defects with broader and more significant aspects to be used.